PERBEDAAN NILAI KERJA GURU LAKI-LAKI DAN PEREMPUAN PADA MADRASAH BERBASIS PESANTREN DI KABUPATEN PONOROGO JAWA TIMUR - Rahmawati Prihastuty; Hanik Musyarofah; Aji Sofanudin (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
Work value is an important thing at work, especially for madrasa teachers. This study aims to determine differences in the work values of male and female teachers as well as the factors forming work values in pesantren-based madrasa teachers in Ponorogo Regency, East Java. This study uses mix methods with 111 subjects of pesantren-based madrasa teachers, consisting of 54 men and 57 women. The research findings show that work values according to male teachers consist of personality quality, religiosity value, academic quality, ukhuwah Islamiyah value, organizational commitment value, professional quality, status, and material value. While the work values of female teachers consist of personality quality, academic quality, professional quality, religious value, organizational commitment value, ukhuwah Islamiyah value, achievement, status, and social value. The factors forming the work values of male teachers are personality, work environment, religiosity, leaders, culture, socioeconomic status, and job satisfaction. The factors forming work values in female teachers consist of work environment, personality, socioeconomic status, culture, leaders, religiosity, reward, and job satisfaction.